Experimental investigation of two novel arrangements of air gap membrane distillation module with heat recovery. (November 2022) - Elhenawy, Y.; Moustafa, G.H.; Abdel-Hamid, S.M.S.; Bassyouni, M.; Elsakka, M.M.
Abstract: Experimental investigations of an air gap membrane distillation (AGMD) unit were carried out to study the energy-saving by heat recovery. The spiral air gap membrane module in the water desalination unit was used. The unit was configured to operate in two novel arrangements and designed to minimize the loss of heat within the drains which maximize the unit productivity as well as the thermal efficiency. Water of salt concentrations 10, 000 ppm and 20, 000 ppm were used. Measurements of the heat source in the form of inlet and outlet temperatures, water productivity, and thermal efficiency are conducted for different flow rates of coolant and water feeds. The new arrangements are found to save much of the supplied heat, minimize the heat loss, and maximize the unit performance. An enhancement of 38.62% in the water productivity was achieved compared to the conventional AGMD unit. The considered heat recovery system showed water productivity of 155.92 m 3 /year for the proposed fresh potable water system with a cost of $12.85 per m 3 .